Genesis and Collapse of a Network. The Rise and Fall of Lucius Aelius Seianus - Köstner, Elena (Journal of Historical Network Research, 2020)
For Roman emperors, loyal advisors in their immediate vicinity were an absolute necessity to ensure good governance. This was the role played by L. Aelius Seianus for emperor Tiberius. Seianus’ exemplary career and climb on the social ladder hit its peak in A.D. 31, when he held the consulship together with Tiberius. A few short months later, he was executed following allegations of plotting against the emperor’s life. With his fall, the networks he had created also disintegrated. This concerned notable figures such as C. Annius Pollio, C. Appius, Iunius Silanus, Mam. Aemilius Scaurus, C. Calvisius Sabinus and L. Annius Vinicianus. This chapter examines Seianus’ networks of support and power, highlighting their dynamics and adaptability.